2023
DOI: 10.1097/pxr.0000000000000248
|View full text |Cite
|
Sign up to set email alerts
|

Prosthesis nonuse and discontinuation in United States veterans with major limb amputation: Results of a national survey

Abstract: Background:Prosthesis use in persons with amputation can improve mobility and functional independence. Better understanding of the reasons for and outcomes associated with prosthesis nonuse is important to optimize function and long-term health in persons with amputation.Objectives:Study objectives were to describe the rate, reasons for, and factors associated with never using or discontinuing prosthesis use in United States (US) veterans with amputation.Study Design:Cross-sectional study design.Methods:The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…11,12 The most recent study by Webster et al in US veterans also noted that female gender was independently associated with increased prosthesis rejection. 9 Although the study did not separate the rejection rate between persons with lower vs. upper extremity limb difference, it reinforced the potential discrepancy between genders. Overall, none of the studies examined found higher rejection rates among men than women with upper extremity amputations.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…11,12 The most recent study by Webster et al in US veterans also noted that female gender was independently associated with increased prosthesis rejection. 9 Although the study did not separate the rejection rate between persons with lower vs. upper extremity limb difference, it reinforced the potential discrepancy between genders. Overall, none of the studies examined found higher rejection rates among men than women with upper extremity amputations.…”
Section: Resultsmentioning
confidence: 88%
“…2,3 One study did reference male, female, and nonbinary respondents to their survey. 9 The terms male/female and women/men are reported in our article as they were reported in the reviewed studies and, for the purpose of our analysis, were treated as equivalent due to lack of ability to distinguish the source information.…”
Section: Resultsmentioning
confidence: 99%